تحديد بعض الخصائص الفيزيائية لفحم أربع أنواع خشبية (Latakia University Journal -Biological Sciences Series, 2018)
The present study aimed to determine the physical properties of charcoal from some wood species (Quercus calliprinos, Olea oleaster , citrus aurantica and Arbutus andrachne ). The charcoal of Quercus calliprinous has heavy weight, harsh surface, section cross shows radial fissured; unclear annual growth rings. Bark was pasted after carbonized. It needs 5 minuets to complete lighting, while the charcoal of Olea oleaster has a medium weight compared with prior species , very harsh surface and the bark was pasted , cross section has strong luster and  very clearly annual growth rings , it needs 6 minuets to complete lighting, whereas the charcoal of citrus aurantica has light weight, smooth, shows clearly both of luster and annual growth rings, moreover it was noted absence of bark, cross section was fissured, lighting was slowly,It needs 6 minutes to complete lighting, the preceding  species were no smoke or smell and they remain firm after glowing for long time more than two hours, regarding the charcoal of Arbutus andrachne it was the lesser weight  compared with others species, smooth, clear luster, cross section shows clearly annual growth rings, radial fissures. It gives sparks during its lighting and needs 8 minuets to have a total glowing and breaks after combustion. The results of physical properties have proved that the charcoal of Quercus calliprinous has the highest value for heat of combustion; moreover, the value of heat of combustion for Charcoal of citrus aurantica is higher than that for the charcoal of Olea oleaster, whereas the charcoal of Arbutus andrachne recorded the lowest value for the heat of combustion. Therefore, the charcoal of Quercus calliprinous was considered the best type of charcoal. The charcoal of Arbutus andrachne gave the highest value for the specific heat capacity. While the charcoal of Quercus calliprinous recorded the lowest value for the specific heat capacity. The specific heat capacity for charcoal of Olea oleaster is lower than that for the charcoal of citrus aurantica. هدفت هذه الدراسة إلى تحديد الخصائص الفيزيائية لفحم بعض الأنواع الخشبية ( السنديان العادي، الزيتون، الليمون الحلو، القطلب) إن فحم السنديان العادي وزنه ثقيل ، سطحه خشن ، مقطعه العرضي أظهر تشققات شعاعية ، حلقات النمو السنوية غير واضحة ، القلف يلتصق بعد التفحيم ، يحتاج إلى 5 دقائق حتى يكتمل اشتعاله ، بينما فحم الزيتون له وزن متوسط بالمقارنة مع النوع السابق ، سطحه خشن جداً والقلف ملتصق به ، مقطعه العرضي لماع بشدة وحلقات النمو السنوي واضحة جداً ، يحتاج إلى 6 دقائق حتى يكتمل اشتعاله ، في حين فحم الليمون الحلو وزنه خفيف، أملس ، أظهر وضوحاً في لمعانه وحلقاته السنوية ، علاوة على ذلك لوحظ غياب القلف ، مقطعه العرضي مشقق ، اشتعاله بطيء ، يحتاج إلى 6 دقائق حتى يكتمل اشتعاله ، الأنواع السابقة لا دخان ولا رائحة لها وتبقى متماسكة بعد توهجها . فيما يتعلق بفحم القطلب فهو أقل وزناً من الأنواع الأخرى، ناعم، ذو لمعان واضح مقطعه العرضي حلقات النمو السنوية بشكل واضح، تشققاته شعاعية. يعطي شرارات خلال اشتعاله ويحتاج 8 دقائق ليكتمل توهجه وهو يتكسر بعد الاحتراق. نتائج الخصائص الفيزيائية أثبتت أن فحم السنديان العادي أعطى أعلى قيمة لحرارة الاحتراق، علاوة على ذلك كانت قيمة حرارة احتراق فحم الليمون الحلو أعلى من حرارة احتراق فحم الزيتون، في حين سجل فحم القطلب أقل قيمة لحرارة الاحتراق، لذلك يعتبر فحم السنديان العادي أفضل نموذج للفحم. فحم القطلب أعطى أعلى قيمة للحرارة النوعية، بينما فحم السنديان العادي سجل القيمة الدنيا للحرارة النوعية. الحرارة النوعية أقل منها في فحم الليمون الحلو.